AMPLICATION OF 0.7KB FRAGMENT KATG GENE FROM CLINICAL MULTI DRUG RESISTANT TUBERCULOSIS ISOLATE IN BALI - Dwiputri, A. W.; Ratnayani, K.; Yowani, and S. C. (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2013)
During last decade has seen a particular increase in the occurrence of drug-resistant of tuberculosis (DR-TB) and multi-DR strains, such as Isoniazid (INH) resistant strains of M. tuberculosis.  INH resistance is more frequently associated with mutations in the katG gene. Detection of katG gene mutations can be performed by PCR technique, followed by sequences. The aim of this study is to amplify katG gene region (0,7 Kb) from clinical isolate of MDR-TB in Bali. DNA isolation for PCR was done by Boom method and katG gene amplification was performed under the following conditions: predenaturation at 950C for 15 min; fourty cycles of denaturation at 940C for 1 min, annealing at 560C for 1 min, extension at 720C for 2 min; final extension at 720C for 10 min. The amplicons were detected by 1.5% agarose gel electrophoresis and showed a specific band size at 0.7 kb. This suggests that the fragment of katG gene has been successfully amplified in these areas.